2018
DOI: 10.3389/fpsyg.2018.00688
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Enriched Light Enhances Alertness but Impairs Accurate Performance in Evening Chronotypes Driving in the Morning

Abstract: Attention maintenance is highly demanding and typically leads to vigilance decrement along time on task. Therefore, performance in tasks involving vigilance maintenance for long periods, such as driving, tends to deteriorate over time. Cognitive performance has been demonstrated to fluctuate over 24 h of the day (known as circadian oscillations), thus showing peaks and troughs depending on the time of day (leading to optimal and suboptimal times of day, respectively). Consequently, vigilance decrements are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 71 publications
1
15
1
Order By: Relevance
“…Lighting, however, did not influence skin temperature in this experiment, in contrast with many previous evidence (Badia et al, 1991; Cajochen et al, 2005; Lockley et al, 2006; Correa et al, 2016; Rodríguez-Morilla et al, 2017, 2018). The main difference between the abovementioned studies and the current one is that participants were at rest in the former while they were engaged in physical activity in all of our conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Lighting, however, did not influence skin temperature in this experiment, in contrast with many previous evidence (Badia et al, 1991; Cajochen et al, 2005; Lockley et al, 2006; Correa et al, 2016; Rodríguez-Morilla et al, 2017, 2018). The main difference between the abovementioned studies and the current one is that participants were at rest in the former while they were engaged in physical activity in all of our conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this evidence becomes weaker at the behavioral level, as many studies have not confirmed that lighting effects improve task performance. A systematic review of the literature has revealed that from 17 studies testing the behavioral effects of bright white light as measured by a simple reaction time (RT) task, such as the psychomotor vigilance task (PVT; Dinges and Powell, 1985), only two of them reported significant effects on RT performance (Souman et al, 2017; see also Rodríguez-Morilla et al, 2018). Other studies using more complex tasks, like the n-back, have also failed to report behavioral effects of light (Vandewalle et al, 2007a,b).…”
Section: Introductionmentioning
confidence: 99%
“…During daytime hours, improvements in alertness may be minimal for well-rested people ( 88 ). Many studies of alertness and cognition have shown mixed results where some measures have improved but others have not ( 15 , 89 92 ).…”
Section: Foundational Considerationsmentioning
confidence: 99%
“…Research into the effects of light on car drivers is scarce and has, thus far, mainly investigated the effects of low-intensity, narrowband blue light during nighttime driving. [37][38][39][40][41] To our best knowledge, only one study has quantified the potential of artificially increased light exposure to increase alertness while driving trucks under naturalistic, daytime conditions. 42 However, no studies to our knowledge have investigated this non-visual effect in passenger cars during the daytime.…”
Section: Study Goalsmentioning
confidence: 99%
“…As a consequence, light impact research in cars during the night has primarily been conducted in driving simulators. 39,40 It can be hypothesised that increasing invehicle light levels during periods of high daylight levels may not evoke arousal effects due to four reasons. First, natural corneal light levels of drivers are high on sunny days (2900 lux; as reported in our unpublished research) and adding light may not have an arousing effect.…”
Section: Limitations Of Our Studiesmentioning
confidence: 99%